Two Faces of Vitamin E in the Lung - Cook-Mills, Joan M. (American Thoracic Society, 2013)
Asthma and allergic lung disease occur as complex environmental and genetic interactions. Clinical studies of asthma indicate a number of protective dietary factors, such as vitamin E, on asthma risk. However, these studies have had seemingly conflicting outcomes. In this perspective, we discuss opposing regulatory effects of tocopherol isoforms of vitamin E, mechanisms for tocopherol isoform regulation of allergic lung inflammation, association of vitamin E isoforms with outcomes in clinical studies, and how the variation in global prevalence of asthma may be explained, at least in part, by vitamin E isoforms.